Effect of 70% alcohol swabbing and flushing technique on high speed contra angle towards bacterial count and identification of pathogens - Mulyanti, Sri (Padjadjaran Journal of Dentistry, 2009)
High-speed contra angle is a potential source of cross-infection due to its working system in blowing up water, saliva and microorganisms from the patients, as well as dental unit water line contamination. This experimental Quasy laboratory study aimed to determine the reduce of bacteria in high-speed contra angle after 70% alcohol swabbing and flushing for 30 seconds and identifying the presence of the pathogen. This study was conducted on 35 lower molar teeth with caries without abscess in patients during pulp opening with the contra-angle. Afterwards, the contra-angle was immersed in sterile aquadest and flushed. The immersed and flushed water were sampled then cultured on blood agar plates. The colony forming units were counted manually: Group I, was the control; Group II, after used on patients; and Group III, after treatment and swabbed with 70% alcohol and flushed. The data were statistically analyzed according to Anava and continued by test with least significant differences (LSD). The results showed that in bacterial identification there were pathogens. The bacteria amount was reduced after swabbing the contra-angle from 50.88±40.33 to 10.31±20.02 cfus. After flushing, the cfus decreased from 169.74±53.76 to 73.03±36.39. Based on the variant and LSD analyzes (p<0.01), CFU was significantly different among the three groups. Conclusion: 70% alcohol swabbing and flushing could reduce the bacterial amount in high-speed contra angle and there was the presence of Staphylococcus aureus and Pseudomonas aeruginosa on the usage of high-speed contra-angle.